Assessment of Water Quality and Trophic Status of Duhok Lake Dam - Baghdad Science Journal (مجلة بغداد للعلوم)
This study is conducted in order to, investigate the trophic state of Duhok Lake Dam located within Duhok city, Iraq. Water samples are collected seasonally from three monitored sites during 2011. The parameters used for assessing water quality and trophic status level include: water temperature, pH, EC, TDS, DO, BOD5, nutrients, Secchi disk transparency, and chlorophyll a. The results reveal that DO is above 5 mg.l-1 in all sites, BOD5 value is within permissible level for domestic uses. Water quality considered as a hard type. High sulfate concentration is recorded during the study period. Trophic state shows that water type is classified as mesotrophic during autumn season, while it is regarded as eutrophic in other seasons. TDN/TDP ratio suggests that phosphorus is a limiting factor for algal growth. Based on IWQI, the water type is classified as excellent type for irrigation purpose.